2024
DOI: 10.1039/d4cp00538d
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical analysis of dual fluorescence and phosphorescence emissions observed for semi-aliphatic polyimides at lower temperatures

Mayuko Nara,
Eisuke Fujiwara,
Aurimas Vyšniauskas
et al.

Abstract: The photoluminescence (PL) properties of four types of blue fluorescent semi-aliphatic polyimides (PIs) derived from aromatic dianhydrides (ODPA, BPDA, HQDEA, and BPADA) and an alicyclic diamine (DCHM) were investigated at...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…We have already reported that both BP-PI and DBrBP-PI are colorless and optically transparent amorphous films. 17,50 The pressure-dependent UV−vis absorption spectra of BP-PI and DBrBP-PI, shown in Figure 7, reveal that the absorption spectra of both PIs red-shifted as the pressure increased. This behavior, consistent with that observed for BP-MC and DBrBP-MC, is attributed to the biphenyl moiety becoming more planar, which extends the π-conjugation length.…”
Section: High-pressure Absorption/emission Spectra Of Polyimidesmentioning
confidence: 99%
“…We have already reported that both BP-PI and DBrBP-PI are colorless and optically transparent amorphous films. 17,50 The pressure-dependent UV−vis absorption spectra of BP-PI and DBrBP-PI, shown in Figure 7, reveal that the absorption spectra of both PIs red-shifted as the pressure increased. This behavior, consistent with that observed for BP-MC and DBrBP-MC, is attributed to the biphenyl moiety becoming more planar, which extends the π-conjugation length.…”
Section: High-pressure Absorption/emission Spectra Of Polyimidesmentioning
confidence: 99%